Elevation of vascular endothelial growth factor and distress in ovarian cancer patients: are they correlated? The pilot trial - G. P. Guens; I. N. Oleynikova; A. S. Kazanova; L. I. Korobkova; I. I. Selezneva; V. V. Kirkin (Опухоли женской репродуктивной системы)
In this pilot trial we analyzed the correlation between neoangiogenesis and psychological status in ovarian cancer patients. We found the correlation between depression levels and serum vascular endothelial growth factor levels in ovarian cancer patients – coefficient of rank correlation (ρ) was 0.42 (95 % confidence interval 0.01–0.72; р < 0,05), that suggests the relationship between this parameters.